2018
DOI: 10.1016/j.envpol.2017.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polystyrene microplastics on early stages of two marine invertebrates with different feeding strategies

Abstract: Nowadays, microplastics represent one of the main threats to marine ecosystems, being able to affect organisms at different stages of their life cycle and at different levels of the food web. Although the presence of plastic debris has been reported in different habitats and the ability to ingest it has been confirmed for different taxa, few studies have been performed to elucidate the effects on survival and development of marine animals. Thus, we explored the effects of different environmental concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(76 citation statements)
references
References 48 publications
1
59
1
1
Order By: Relevance
“…The presence of µPs in different environmental matrices and their small size can result in the ingestion by organisms. A wealth of studies has demonstrated the ingestion of different µP items in 160 marine species (see Lusher 2015 and reference therein), including fish (Collard et al 2017), seabirds (Lavers et al 2014), mammals (Fossi et al 2012) and invertebrates (Graham et al 2009;Cole et al 2013;Messinetti et al 2018), as well as in 39 freshwater species (Scherer et al 2017). Experimental studies have also demonstrated that µPs ingestion might negatively affect the health status of aquatic species, including fish (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of µPs in different environmental matrices and their small size can result in the ingestion by organisms. A wealth of studies has demonstrated the ingestion of different µP items in 160 marine species (see Lusher 2015 and reference therein), including fish (Collard et al 2017), seabirds (Lavers et al 2014), mammals (Fossi et al 2012) and invertebrates (Graham et al 2009;Cole et al 2013;Messinetti et al 2018), as well as in 39 freshwater species (Scherer et al 2017). Experimental studies have also demonstrated that µPs ingestion might negatively affect the health status of aquatic species, including fish (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…PP-fibers generally induced significantly increased mortality, while the PE-spheres, PS-spheres, and the PP-fragments affected mortality rates in a size-dependent manner with larger particles being responsible for significant effects exclusively ( Table 2). Lethal effects of PS-and PE-spheres were also assessed in Ciona robusta (Chordata; Messinetti et al, 2018), Paracentrotus lividus (Echinodermata; Messinetti et al, 2018) and Tripneustus gratille (Echinodermata; Kaposi et al, 2014; Table 2), with no effects being observed. Among the investigated marine molluscs, no lethal effects induced by a variety of plastic particles could be found ( Table 2).…”
Section: Mortalitymentioning
confidence: 99%
“…Additionally, effects of PS-spheres have further been reported to be size-dependent as indicated for the intergenerational developmental responses of T. japonicas (Lee et al, 2013) and development time of P. nana (Jeong et al, 2017), with both parameters being affected by nanosized spheres exclusively ( Table 2). However, studies examining the impact of small-scale plastics on echinoderms reported significant dose-dependent effects for a variety of applied particles, such as PS-spheres on T. gratilla (Kaposi et al, 2014), and significantly affected development of P. lividus exposed to plain PS-spheres (Martínez-Gómez et al, 2017;Messinetti et al, 2018), nanospheres of functionalized PS particles (PS-NH 2 ; Della Torre et al, 2014) and HDPE-fragments (Martínez-Gómez et al, 2017). In terms of PS-spheres, comparable results were reported for the ascidian C. robusta, with a significant delay in juvenile development but no effects on larvae (Messinetti et al, 2018; Table 2).…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unclear if sphincters are present in either of these groups. While, the behavior of ingested microbeads indicates a regulated barrier lies between the stomach and the intestine (12). As sea urchins have a distinct pyloric sphincter, they are tractable models for investigating gut formation and function.…”
mentioning
confidence: 99%